Youth participation in plantation sector; a qualitative study in Jasin, Melaka / Amirul Hadi Noorhadi - Noorhadi, Amirul Hadi (Faculty of Plantation and Agrotechnology, 2018)
Youth is the savior of nation’s future economy thus government, industry player and practitioner play important roles in eliminating obstacles that reduce youth empowerment towards expedite National Transformation (TN50). Their participation in Malaysia plantation sector is significantly low level because they prefer working in others sector which is less dangerous, difficult and dirty (3D). The aims of this research are to identify the pull and push factors and the perspective towards this industry. Qualitative data were collected through a semi-structured interview of five participants ranging 20-25 years old from developed areas who have graduated with diploma or degree certificate and is currently working part time or full time. Purposive sampling technique was used to identify various informants. The finding reveals the importance of youths to sustain the national economy, by providing sustain production for Malaysia food security. While at the same time, limitation factors (ie., implementation of Occupational Safety and Health Act (OSHA), foreign workers, working environment, background qualification and interest) should be eliminated. Desired extrinsic factors which motivate youths (ie., salary, technology approaches and good accommodation) need to be fulfilled with the involvement of all parties; family, society and government as a whole to enhance youth participation in plantation sector.